Support Obtained by Families in Running Palliative Care Programs for Advanced Cancer Patients at Home - Dasat, Mariam; Mulyono, Sigit; Khasanah, Uswatul; Hermawan, Stepanus Maman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Palliative care is a service provided to improve the quality of life of patients both physically, psychologically, socially and spiritually. The purpose of this study is to identify the support obtained by families in carrying out palliative care programs for advanced cancer patients at home. This study uses qualitative research design with phenomenological approach with data collection techniques through in-depth interviews with six participants. Data retrieval using snow ball sampling. Found 5 themes of support obtained by families in caring for advanced cancer patients, namely financial support from people around, moral support from people around, support from health workers and hospitals, helping household chores and patients wanting to stay healthy. The palliative care program carried out by families to patients is good because it has received support from health workers, other family members and neighbors or close relatives so that the goal of cancer palliative care is achieved, namely improving the quality of life of patients by meeting physical, psychological, social and spiritual needs.